7y+y+14=8y-4+3y

Simple and best practice solution for 7y+y+14=8y-4+3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+y+14=8y-4+3y equation:


Simplifying
7y + y + 14 = 8y + -4 + 3y

Reorder the terms:
14 + 7y + y = 8y + -4 + 3y

Combine like terms: 7y + y = 8y
14 + 8y = 8y + -4 + 3y

Reorder the terms:
14 + 8y = -4 + 8y + 3y

Combine like terms: 8y + 3y = 11y
14 + 8y = -4 + 11y

Solving
14 + 8y = -4 + 11y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11y' to each side of the equation.
14 + 8y + -11y = -4 + 11y + -11y

Combine like terms: 8y + -11y = -3y
14 + -3y = -4 + 11y + -11y

Combine like terms: 11y + -11y = 0
14 + -3y = -4 + 0
14 + -3y = -4

Add '-14' to each side of the equation.
14 + -14 + -3y = -4 + -14

Combine like terms: 14 + -14 = 0
0 + -3y = -4 + -14
-3y = -4 + -14

Combine like terms: -4 + -14 = -18
-3y = -18

Divide each side by '-3'.
y = 6

Simplifying
y = 6

See similar equations:

| 2a/3b-c= | | 4=-6v+8(v+2) | | -8x+4(x-3)=-8 | | 8y+8y=24 | | -5x+3=-47 | | -75+4x+6x=25 | | Y(2)+3y(2-1)=e(2) | | Y(1)+3y(1-1)=e(1) | | 5x-3x-19=11 | | 81+w=10w | | 12u=24+9u | | 5(3y-4)=10 | | 4s+3s-9s=22 | | 4=10m | | -6x-2x=48 | | Y(0)+3y(0-1)=e(0) | | 30=9m | | (-9p-1)-(-2p-5)= | | b/10=20 | | 6u=1+3 | | -7(-m-3)=46 | | 5(x+0.40)=5 | | 6x-6=-24+2x | | X+9+(-11)=2 | | (5-2i)/(1-3i) | | 56=5w+16 | | -2+3y=-23 | | 26=x/4-17 | | cot(10x)=cot(5x) | | 5x(4.1+b)=45 | | tan(10x)=tan(5x) | | 67.2=3.5*q |

Equations solver categories